Evaluation Of Ground Water Of Khunwade And Bordi Of Dahanu Taluka, Maharashtra, On The Basis Of Piper Trilinear Diagram - Gogari P. K., Chaudhari V. S. , Save S. N. (International Journal of Advanced Science and Technology, 2020)
Water, the most vital resource for all kinds of life on this planet is also the resource, adversely affected both qualitatively and quantitatively by all kinds of human activities on land, in air or in water. The quality of groundwater is as important as the quantity.The study area Dahanu is last surviving green zone between Mumbai and Surat. Its 47% of area is under forest cover. As per 2001 census, the population of Dahanu taluka is 3,31,829 of which 55% is tribal. Till date, the economy of Dahanu, Gholwad, and Bordi survives on its sapodilla (chikoo) plantations as seven out of ten chikoos of the country grow here. About 37 thousand tons of chikoo are produced per month and are dispatched to Mumbai, Delhi, Ahmedabad, Jaipur, Udaipur and Pune. (www.dahanu.com). Irrigated agriculture depends on an adequate water supply of usable quality. The quality parameters are many times neglected as good quality water supplies have been plentiful and readily available. But the situation is now changing in many areas at an alarmingly fast rate. There are several graphical methods that are used for visualization and classification of hydro chemical data. One of the most widely accepted of these is the Piper trilinear diagram (Piper 1944; Hill1940). This diagram has three parts: a cation triangle, an anion triangle, and a central diamond-shaped field. Water samples were collected from 26 locations during pre and post monsoon period of 2008. The study aims to classify ground water on the basis of combined effect of electrical conductivity (E.C.) and Sodium Adsorption Ratio (S.A.R.) to check its suitability for irrigation. Introduction There are several graphical methods (Zaporozac 1972 Gu ¨ler et al. 2002) that are used for visualization and classification of hydrochemical data. The most widely accepted of these is the Piper trilinear diagram (Piper 1944; Hill 1940). This diagram has three parts: a cation triangle, an anion triangle, and a central diamond-shaped field (Figure 1). Similar to the Piper diagram is the diagram proposed by Durov (1948), where the sample points on associate